2010
DOI: 10.1016/j.jbiomech.2010.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive relationship of tissue behavior with damage accumulation of human cortical bone

Abstract: Microdamage accumulation has been identified as a major conduit for bone tissues to absorb fracture energy. Due to the poor understanding of its underlying mechanism, however, an adequate constitutive relationship between damage accumulation and the mechanical behavior of bone has not yet been established. In this study, the constitutive relationship between the damage accumulation induced by overload and the evolution of mechanical properties of bone with incremental deformation was established based on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
(49 reference statements)
0
14
0
2
Order By: Relevance
“…[1], [2], [3], [4] Several studies have reported microdamage in human trabecular bone occurring naturally. [5], [6], [7], [8], [9], [10] Increased microdamage is associated with decreased bone strength in vitro, and thus may play a role in fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
“…[1], [2], [3], [4] Several studies have reported microdamage in human trabecular bone occurring naturally. [5], [6], [7], [8], [9], [10] Increased microdamage is associated with decreased bone strength in vitro, and thus may play a role in fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
“…When the damaged trabecular bone underwent creep loading, stress distribution within the bone will be rearranged, resulting in stress concentration and new fracture in undamaged trabeculae [32,33]. Evidence suggests that stress rearrangement depends on degree of bone damage [34]. Stress rearrangement in bone was negligible when modulus reduction was below 30%, but became significant if modulus reduction was greater than 30% [34].…”
Section: Explanation Of Resultsmentioning
confidence: 99%
“…For this study, an intermediate value of 1.2 was selected. J 1 and ′ J 2 are strain invariants defined as (4) where ε − eq MAX is the highest equivalent strain encountered in the loading history. The form of the equation is similar to that used in a previous quasi-brittle damage model of bone.…”
Section: The Quasi-brittle Materials Modelmentioning
confidence: 99%
“…Osteoporotic hip fractures are an important source of morbidity and mortality, and understanding the mechanisms surrounding hip fracture may help to develop more effective preventative intervention strategies. Material level studies have demonstrated that the structural response of bone is history dependent . As bone material is loaded, it suffers progressive damage in the form of micro‐fractures .…”
mentioning
confidence: 99%
See 1 more Smart Citation